Accelerated composition-process-properties design of precipitation-strengthened copper alloys using machine learning based on Bayesian optimization - Longjian Li; Jinchuan Jie; Xiaoyu Guo; Gaojie Liu; Huijun Kang; Zongning Chen; Enyu Guo; Tongmin Wang (Materials Research Letters)
Designing new alloys with high performance is challenging due to the large search space for composition and process parameters. We propose an alloy design strategy based on machine learning algorithms for navigating the enormous search space. Specifically, feature engineering was applied to screen the major features, and a three-step alloy design strategy was employed to extract the required composition. The material design strategy for the multi-performance optimization of Cu-Ni-Si alloy through Bayesian optimization was proposed. This work provides novel insights into the comprehensive properties of Cu-Ni-Si alloys using machine learning with small data, with potential applicability to other materials systems.